APPLICATION OF COGNITIVE DIAGNOSTIC ASSESSMENT TO MEASURE THE READINESS OF MATHEMATICS LEARNERS AT THE JUNIOR HIGH SCHOOL LEVEL WITH THE SMART APPS CREATOR APPLICATION - Jajang Rahmatudin; Efi Jumaesari; Ela Nurcholisyah; Ervita Dian Pramesti; Hesty Marliana Wati; Hesty Umi Wulandari; Linda Permatasari; Liya Puji Suciani,; Magfiroh Magfiroh; Nurlela Nurlela (Jurnal Abdisci, 2026)
Background. Students' learning readiness is an important factor in supporting the success of mathematics learning at the junior high school (SMP) level. However, the implementation of cognitive diagnostic assessments in schools remains suboptimal in terms of methodology, accuracy, and sustainability. Purpose. This study aims to apply technology-based cognitive diagnostic assessment using the Smart Apps Creator application to measure students' readiness for mathematics learning in a more systematic and integrated manner. This activity was carried out at SMP Negeri 2 Plumbon and SMP Negeri 2 Plered in Cirebon Regency, involving teachers and students as the main participants. Method. The methods used include the observation stage, planning, data collection, product design, validation, trial, revision, and implementation. The assessments developed are integrated with Microsoft Excel to facilitate the processing and analysis of learning outcome data. Results. The results of the activity showed that the application of cognitive diagnostic assessments based on Smart Apps Creator increased the effectiveness of measuring students' learning readiness and assisted teachers in identifying learning characteristics and needs more accurately. Conclusion. The use of this technology also improves teachers' competence in designing and analyzing assessments in a sustainable manner. Implementation. The application of cognitive diagnostic assessments through digital applications can be an innovative solution to support more adaptive, needs-oriented mathematics learning.